2015
DOI: 10.2500/ajra.2015.29.4185
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of 11β-Hydroxysteroid Dehydrogenase Type 1 and 2 in Nasal Polyp–Derived Epithelial Cells and its Possible Contribution to Glucocorticoid Activation in Nasal Polyp

Abstract: Analysis of these results indicated that 11β-HSD1 expressed in polyp-derived epithelial cells may be involved in the anti-inflammatory function of glucocorticoid in the treatment of nasal polyps, which contributes to increased levels of endogenous cortisol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this line, intrapolyp steroid injections appear to be effective and safe for the treatment of nasal polyps (Kırıs et al, 2016). Additionally, it has been shown that polypderived epithelial cells produce cortisol, which may be involved in the anti-inflammatory response established when patients receive treatment with glucocorticoid for nasal polyps (Kook et al, 2015). The elevation of this metabolite in the non-allergic CRSwNP patients might point to a specific pathway to cope with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, intrapolyp steroid injections appear to be effective and safe for the treatment of nasal polyps (Kırıs et al, 2016). Additionally, it has been shown that polypderived epithelial cells produce cortisol, which may be involved in the anti-inflammatory response established when patients receive treatment with glucocorticoid for nasal polyps (Kook et al, 2015). The elevation of this metabolite in the non-allergic CRSwNP patients might point to a specific pathway to cope with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies like this should ultimately lead to new and more effective therapies for CRS, but the mainstay for medical management continues to be glucocorticosteroids. In this issue, Kook et al 2 assess polyp-derived epithelial cell expression of enzymes involved in glucocorticosteroid metabolism and correlate enzyme expression with cortisol levels. Their results suggest that expression of the enzyme 11β-hydroxysteroid dehydrogenase may mediate the anti-inflammatory effect of glucocorticosteroids by increasing levels of endogenous cortisol.…”
mentioning
confidence: 99%